Northup’s Resistance Towards Racial Discrimination in Twelve Years a Slave - Rahmat Hasan; Tahir Tahir (Journal of Research and Multidisciplinary, 2022)
This research is sociological literary research and focuses on Lucien Goldmann’s genetic structuralism which sees the literary work as the reflection of the sociological background and condition of the society of the author. Afterward, the researcher also sees the literary work as a social document that reflects the situation when the literary work was produced. Therefore, this research aims to find: 1. Forms of racial discrimination experienced by Solomon Northup as it is shown in Twelve Years a Slave; 2. How the phenomena of slavery in America during the Pre-Civil War Period significantly plays a prominent part as shown in Twelve Years a Slave. The researcher found the forms of racial discrimination toward Solomon Northup and other African-American slaves namely prejudice, discrimination, segregation, and violence. Furthermore, the researcher found that the phenomenon of slavery significantly plays a prominent part in the writing of Twelve Years a Slave. The characteristic of the Pre-Civil War, the economic features, the lifestyles of the north and south, and the rise of the abolitionist movement were all considered to be the aspects that link the society and the writing progress of Twelve Years a Slave.